EFFECTS OF ATORVASTATIN IN PATIENTS WITH RHEUMATOID ARTHRITIS AND DYSLIPIDEMIA - N. M. Nikitina; A. P. Rebrov (Klinicist)
Objective: to evaluate the basic and pleiotropic effects of atorvastatin in patients with rheumatoid arthritis (RA) and dyslipidemia (DLP).Subjects and methods. The blood lipid profile was studied in 204 patients with RA. According to the found lipid disturbances, the patientswere randomized into 2 groups. A study group comprised 30 patients receiving generic atorvastatin 10 mg/day as part of combination therapy.A comparison group included 20 RA patients matched for clinical characteristics and baseline lipid levels, who took no statins. Blood lipidparameters and the markers of inflammation, vascular wall damage, and artery rigidity were examined over time.Results. DLP was found in 58.3 % of the patients with RA. The use of atorvastatin in combination therapy resulted in not only a decrease in atherogenic cholesterol fractions, but also in a considerable reduction in the level of the markers of systemic inflammation and endothelial damage, and in disease activity. Six-month atorvastatin therapy showed a positive impact on the elastic properties of vessels in RA patients.Conclusion. In RA patients with DLP, atorvastatin exerted a beneficial effect not only on the blood lipid profile, but also on the magnitude of inflammation and the elastic properties of vessels, and disease activity.